Analisis Efektivitas Program BPJS Kesehatan Dalam Meningkatkan Kesehatan dan Kesejahteraan Masyarakat - Irna Permata Sari; Fauzi Arif Lubis; Khairina Tambunan (LPPM Institut Nasional Laa Roiba Bogor, 2024)
The purpose of this study is two. The first is to find out how effective the BPJS Health program is based on input, process, and output indicators. The second is to know how the community of users of the BPJS Health program sees the benefits they get. In this study, descriptive qualitative research methods are used. Researchers use the theory of post-positive qualitative research as the primary tool for assessing the state of a reasonable thing. The sample consisted of 15 people who answered the question. The results of the analysis show that Labuhanbatu North service facilities, procedures, and responses related to the service process, quality, reliability, and accessibility can affect the level of effectiveness of the BPJS Health program. The BPJS Kesehatan program also helps its participants by lowering treatment costs, boosting health levels, enhancing service quality, and facilitating simpler access to healthcare. Keywords: Effectiveness, Health, Welfare of the Social Security Administration Agency (BPJS)